2003
DOI: 10.1002/bjs.4044
|View full text |Cite
|
Sign up to set email alerts
|

Smoking affects the outcome of transanal mucosal advancement flap repair of trans-sphincteric fistulas

Abstract: Cigarette smoking affects the outcome of TAFR in patients with a cryptoglandular perianal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
1
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 10 publications
7
74
1
7
Order By: Relevance
“…Earlier larger studies on endoanal advancement flap repair for anal fistula described low recurrence rates of 1-16 per cent 1 -3 , but in three later studies by Sonoda et al 9 , Mizrahi et al 10 and Zimmerman et al 18 , each of which included around 100 patients, recurrence rates were 36, 40 and 31 per cent respectively. In a smaller previous study that included 42 patients with mostly cryptoglandular, trans-sphincteric fistulas, the rate of nonhealing was 45 per cent 11 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Earlier larger studies on endoanal advancement flap repair for anal fistula described low recurrence rates of 1-16 per cent 1 -3 , but in three later studies by Sonoda et al 9 , Mizrahi et al 10 and Zimmerman et al 18 , each of which included around 100 patients, recurrence rates were 36, 40 and 31 per cent respectively. In a smaller previous study that included 42 patients with mostly cryptoglandular, trans-sphincteric fistulas, the rate of nonhealing was 45 per cent 11 .…”
Section: Discussionmentioning
confidence: 96%
“…In most studies that included both cryptoglandular and Crohn's fistulas, patients with Crohn's disease had higher recurrence rates 2,9,10,19 . Schouten et al 20 found that patients with more than one previous fistula repair had significantly higher recurrence rates than those with one or no previous repair (50 versus 13 per cent respectively), but in a later study by the same group there was no difference 18 . In other studies, in which the proportion of patients with previous repairs varied between 15 and 47 per cent, earlier repair had no impact on the recurrence rate 3,9 -11 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In order to avoid this, mucosal advancement flap procedure was introduced in the treatment of recurrent transsphincteric and suprasphincteric cryptogenic perianal fistulas. Although no authors reported success rates exceeding *70 % [80,81], the outcome of this procedure was considered satisfactory until 2011 when Jarrar and Church [82] reported a success rate of 98 % in the treatment of cryptogenic fistulae, performing in some cases two or three mucosal advancement flap operations.…”
Section: Perianal Fistulasmentioning
confidence: 99%